Causes and Solutions of Poverty in Uzbekistan - Achilova, R. A. (International Journal on Integrated Education, 2023)
This article covers the problem of population poverty, which has been a "closed topic" in Uzbekistan for many years. Based on the study of the concept of "poverty", the criteria for defining it and the ways to reduce it have been thoroughly studied. Possibilities of using foreign experiences to reduce poverty in Uzbekistan are described. Additional comments and suggestions have been made on this topic.